(untitled) (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2024)
Background: Impact of babies born with low birth weight is the growth rate will slow. Factors - risk factors that affect the incidence of LBW among other things is the social characteristics of maternal demographic, medical risk mothers before pregnancy also contribute to the incidence of LBW, and the status of antenatal care. The research goal is to know the factors associated with the incidence of LBW in Riau Prov Arifin Achmad Hospital in 2013-2014. Method: This type of study is a case-control study design (Case Control Study). Cases of infants born with LBW in Riau Prov Arifin Achmad Hospital in 2013-2014 and Control of babies born with normal weight at the Arifin Achmad Year 2013-2014. Result: The study maternal Hb <11 g% more at risk of having a baby with low birth weight 14 times compared to mothers who have a Hb> 11 gr% (OR = 13.895 (95% CI 8.061 to 23.950), mothers who have a spacing of <2 years are more at risk of giving birth low birthweight infant 15 times compared to mothers who have a spacing of ≥ 2 years (OR = 15.138 (95% CI: 9.024 to 25.392), including women who are at risk age category (age <2 years and age> 35 years) were more at risk of having a baby with LBW 5 times compared to mothers who did not include at-risk age category (age 20 to age 35 years) (OR = 5.266 (95% CI: 3.423 to 8.100), mothers classified as at risk parity (parity 0 and parity> 4) more at risk of having a baby with low birth weight 8 times compared to mothers who did not belong to the category of risky parity (parity 0 and parity> 4), OR = 7.606 (95% CI: 4.847 to 11.936), mothers who never attended school, elementary education, junior high is more risky gave birth to babies with low birth weight 7 times compared to women whose education high school and PT, OR = 6.921 (95% CI: 4.426 to 10.823). Conclusion: The study maternal Hb ,11gr%, mothers who never attended school elemenary education and junior high school, mothers who have a spacing op > 2 years, mothers classified as at risk parity 0 and parity 4, including woman age category>35 years old were more at risk of having a baby with LBW. Keywords: factors, the incidence of LBW